Effects of Short Chain Fatty Acid-Butyrate Supplementation on the Disease Severity, Inflammation, and Psychological Factors in Patients With Active Ulcerative Colitis: A Double-Blind Randomized Controlled Trial - Donya Firoozi; Seyed Jalil Masoumi; Seyed Mohammad-Kazem Hosseini Asl; Mohammad Fararouei; Sanaz Jamshidi (Journal of Nutrition and Metabolism)
Trial Registration: Iranian Registry of Clinical Trials: IRCT20211214053401N1